Evaluating the Role of Individualized Homoeopathic Treatment in the Management of Cystitis: A Case Study - Dr. Janakiben Bhanvadia; Dr. Kirtida Desai (The Bioscan, 2025)
Recurrent urinary tract infections are of importance for public health as most clinicians are faced with repeated and long term administration of broad-spectrum antimicrobial agents leading to an increased risk of resistant bacteria. Widespread use of antibiotics has led to the emergence of resistant microorganisms. As the antibiogram of the microorganisms are frequently changing so it creates a huge opportunity for the therapeutic sciences such as Homoeopathy who doesn’t rely on the entity of causative microorganisms. Homoeopathy, with its individualized system of prescribing, has shown potential benefits, especially when combined with supportive measures. This case report describes the management of a patient with acute cystitis treated with the homoeopathic remedy Lycopodium. Prescription was based on a thorough case analysis, taking into account both physical complaints and general health. Alongside dietary guidance and auxiliary advice, the individualized medicine led to a notable reduction in symptoms. Symptomatic improvement was observed within a short span of treatment, and no side effects were reported. The findings from this case highlight the scope of individualized homoeopathic treatment in acute cystitis. When integrated with simple lifestyle measures, it may provide safe and effective relief while supporting long-term well-being. Further clinical studies could strengthen evidence for its broader application. KEYWORDS Cystitis, Homoeopathy, Lycopodium, Acute Cystitis symptom score (ACSS)